Science teachers' narratives in developing students' creative thinking and autonomy in research classes - Capisnon, Ruben B. Jr.; Paderna, Edwehna Elinore S.; Ramirez, Rachel Patricia B.; Oyzon, Maria Vanessa P. Lusung (Quezon City College of Education, University of the Philippines, Diliman, 2023)
"Teaching the Research subject to students is not for mere compliance with the curriculum mandates but also to develop lifelong skills. Conducting research allows students to utilize these skills while being exposed to authentic learning activities and problem-based tasks. Two of the important skills to be developed in teaching Research in distance learning delivery modality are creative thinking and learner autonomy. This study utilizes the narratives of science teachers who have served as coaches of winning science investigatory projects during the pre-pandemic setup. They have shared their best practices in conducting online Research classes, the activities they implemented to develop students' thinking and autonomy skills, and the indicators that helped them describe creative thinkers and autonomous learners. Results have revealed that Research classes were conducted through distance learning delivery modality, the preparations done were school-initiated, stakeholders-involved, and personal, documents such as self-learning modules and Weekly Home Learning Plan were used, the schedule of classes were done both synchronously and asynchronously, assessments were administered through written outputs and performance tasks. Activities that developed students' creative thinking were differentiating ideas, setting goals and expectations, rewarding commendable performance, reflecting on self-and peer's performance, and fostering collaboration among peers. Meanwhile, activities for learner autonomy development were managing peers, promoting dialogue in the class, decision-making, initiating self-learning, and evaluating oneself. The science teacher-coaches describe students who are creative thinkers if they are capable of generating unique topics, resourceful in crafting solutions, and able to identify societal problems. On the other hand, a student is considered an autonomous learner if they are able to work with little assistance from an authority, perform beyond expectations, and prefer working alone or in small groups. Recommendations were to utilize the themes generated from this study to improve teaching strategies being implemented in distance learning delivery modality, to conduct a quantitative study, and to investigate the development of these skills in other discipline or different learning modalities." --
Thesis
Includes bibliographic reference (112-128 leaves)
Keywords: Science teachers -- In-service training -- Philippines; Science -- Study and teaching (Secondary) -- Philippines; Internet in education -- Philippines; Science -- Research